PENGEMBANGAN MODUL BIOLOGI SEKOLAH: EKOLOGI, MIKROBIOLOGI DAN PLANTAE BAGI CALON GURU - Riski Karmila; Evi Suryawati; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the quality of school biology modules: ecology, microbiology and plantae for prospective teachers. This research was conducted at the Biology Education Study Program Department of Mathematics and Natural Sciences Faculty of Riau University and the Subject Teachers' Association (MGMP) Pekanbaru City in October 2019-March 2020. This type of research refers to the Research and Development (R&D) research approach using the ADDIE model with Analyze stages, Design, Develop, Implement, and Evaluate. This research was only carried out until the Develop phase by validating by the validator, a limited trial of stages I and II of undergraduate biology education students at FKIP Riau University. The instruments used were validation sheets and response questionnaires. Descriptive data analysis. The quality of the modules developed is assessed from 5 aspects namely the module format, graphic, illustration, language, and content worthiness aspects. Module quality based on validity is decent with a score of 3.29 very valid categories. The module used from the results of the limited trial phase I gained a score of 3.48 with a very good category and stage II gained a score of 3.52 with a very good category. Based on these data it can be concluded that the quality of the school biology modules: ecology, microbiology and plantae for prospective teachers is very good and deserves to be a source of independent learning in preparation for participating in the PPG selection to be carried out in order to achieve predetermined competency standards.Key Words: School Biology, Prospective Teacher, Modules